2014
DOI: 10.1039/c4tb00125g
|View full text |Cite
|
Sign up to set email alerts
|

Development of superoxide dismutase mimetic surfaces to reduce accumulation of reactive oxygen species for neural interfacing applications

Abstract: Despite successful initial recording, neuroinflammatory-mediated oxidative stress products can contribute to microelectrode failure by a variety of mechanisms including: inducing microelectrode corrosion, degrading insulating/passivating materials, promoting blood-brain barrier breakdown, and directly damaging surrounding neurons. We have shown that a variety of anti-oxidant treatments can reduce intracortical microelectrode-mediated oxidative stress, and preserve neuronal viability. Unfortunately, short-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 64 publications
0
56
0
Order By: Relevance
“…Previous reports have suggested that both free 33,34 and immobilized 22 antioxidants decrease inflammation and improve neuronal health at the site of implantation. Increasing the surface antioxidant concentration and antioxidant activity may allow for a greater effect of immobilized antioxidant coatings.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous reports have suggested that both free 33,34 and immobilized 22 antioxidants decrease inflammation and improve neuronal health at the site of implantation. Increasing the surface antioxidant concentration and antioxidant activity may allow for a greater effect of immobilized antioxidant coatings.…”
Section: Resultsmentioning
confidence: 98%
“…Nanopatterned surface ridges on silicon implants have been shown to reduce the activity of astrocytes in vitro , 19 while surface topographic features can guide neurite outgrowth and alignment. 20,21 Meanwhile, superoxide dismutase mimics such as Mn( iii )tetrakis(4-benzoic acid)porphyrin and amine functionalized meso -tetra(2-pyridyl)porphine (referred to as iSODm) 22,23 have been covalently bound to the surface of neural implants to reduce harmful reactive oxygen species (ROS) released both acutely after insertion injury and chronically as a component of inflammatory tissue responses. Biomimetic coatings utilizing peptides 24,25 and proteins 10,26,27 exhibit pronounced effects in reducing the inflammatory response and/or encouraging neurite attachment as well as decreasing the activation of glia.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in order to determine the concentration of resveratrol, a fluorescent spectrophotometric analysis was utilized following previously published protocols with minor alterations(Delmas et al, 2011; Potter-Baker et al, 2014a). For all analysis, samples were read in 96-well black plates at an excitation of 315 nm and an emission of 385 nm.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, our group has begun to investigate the use of anti-oxidative approaches to mitigate the buildup of reactive oxygen intermediates around implanted microelectrodes(Potter et al, 2013; Potter-Baker et al, 2014a; Potter et al, 2014). Specifically, we have found that short-term (<48 hours) accumulation/release of anti-oxidants, for example resveratrol or curcumin, around implanted microelectrodes can result in higher densities of neuronal nuclei and more viable neurons at the device interface (Potter et al, 2013; Potter et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…have shown that the incorporation of YIGSR in polypyrrole coatings result in more neuron survival at the electrode site compared to control sites (Cui et al, 2003). He et al demonstrate that electrostatically deposited laminin (He et al, 2006) and α-MSH functionalized using silane chemistry (He et al, 2007) result in a less intense glial scar as measured by immunohistochemistry and cytokine measurements Recent insights into the factors involved in the reactive tissue response suggest a potentially wider range of biomimetic approaches, such as superoxide dismutase mimetic surfaces to reduce accumulation of reactive oxygen species (Potter-Baker et al, 2014). …”
Section: Drug Delivery and Biomimetic Approachesmentioning
confidence: 99%